Recognition on pharmacodynamic ingredients of natural products - Tao Wang; Zhong-Yu Fu; Yan-Juan Li; Lei Zi; Cheng-Zhu Song; Yu-Xuan Tao; Mei Zhang; Wen Gu; Jie Yu; Xing-Xin Yang (Elsevier, 2024)
Natural products (NPs) play an irreplaceable role in the intervention of various diseases and have been considered a critical source of drug development. Many new pharmacodynamic compounds with potential clinical applications have recently been derived from NPs. These compounds range from small molecules to polysaccharides, polypeptides, proteins, self-assembled nanoparticles, and extracellular vesicles. This review summarizes various active substances found in NPs. The investigation of active substances in NPs can potentiate new drug development and promote the in-depth comprehension of the mechanism of action of NPs that can be beneficial in the prevention and treatment of human diseases.